Effect of Different Sources of Zinc on Growth Performance and Hemato-Biochemical Profiles in Murrah Buffalo Calves - Kumar, Atul; Sahu, DS; Chandra, Gulab; Yadav, SP; Kumar, Raj; Jaiswal, Vikas; Maurya, Premsagar; Singh, Rakesh Kumar (Indian Journal of Animal Nutrition, 2018)
Eighteen 12-15 months old buffalo calves were used to compare the effects of inorganic and organic zinc (Zn) supplements on growth performance, hemato-biochemical profile. Calves provided three diets in a randomized block design: basal diet with no supplemental Zn (control), basal diet plus 40 mg Zn/kg dry matter as zinc sulfate hepthydrate (ZS) and basal diet plus 40 mg Zn/kg dry matter as zinc methionine (ZM) for 90 days. Body weight and feed consumption were not significantly different between treatments. Body weight gain (BWG) was higher (P<0.05) in ZM and ZS group than control group. Feed conversion ratio (FCR) was observed lower (P<0.05) in Zn supplemented group either zinc sulphate or zinc methionine than control. Hemoglobin (Hb) concentration was showed significance (P<0.05) difference between treatments. Packed cell volume (PCV), total erythrocyte count (TEC), total leukocyte count (TLC), neutrophil, and lymphocyte were higher (P<0.05) in ZM and ZS groups than its level observed in control group. Basophil, eosinophil, and monocyte were not significance difference between the groups. Total protein, globulin, and glucose concentration in ZM and ZS groups were higher (P<0.05) than its level observed in control, but there was significance differences ZM and ZS groups. Plasma concentration of albumin and total immunoglobin (TIG) was showed significant difference between the groups and observed higher concentration in ZM group. Buffalo calves that received zinc methionine show improved immunological status as compared to control.